Lineamientos de trabajo seguro en procesos administrativos, operativos y académicos por medio de Guías Estándar de Trabajo Seguro (Universidad Antonio Nariño - Sede Villavicencio, 2020) - Archbold Calderón, David Santiago; Chitiva Enciso, William Alexander (Universidad Antonio Nariño, 2021)
The objective of this degree work was to structure safe work guidelines for the administrative, operational and academic processes carried out by the collaborators of the Universidad Antonio Nariño – Sede Villavicencio. For this purpose, the procedures performed by the workers were identified by means of a job description questionnaire. Then, they were provided with a sociodemographic profile questionnaire and a questionnaire on safety and health conditions at work, to identify the dangers to which workers were exposed throughout their working hours. To complement this information, the Koys and Decottis questionnaire was also applied to measure organizational climate and the VHI-10 questionnaire was applied to teachers to measure the dysphonia perceived by them. With this information, a hazard identification and risk assessment matrix was constructed, which were evaluated using the Fine method. Finally, all the information collected was used to structure the documents called Standard Safe Work Guides, which contain the key safety points that workers must follow to protect their human well-being. These guides have in common the presence of ergonomic measures required for the execution of administrative activities, in addition to other measures related to security conditions in positions of an operational nature. And given the current sanitary conditions, they include biosafety protocols supported by current Colombian legislation.